2022
DOI: 10.4103/ijo.ijo_2014_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of newer Kane formula with Sanders Retzlaff Kraff/Theoretical and Barrett Universal II for calculation of intraocular lens power in Indian eyes

Abstract: Purpose: To compare the efficacy of Kane formula with Sanders Retzlaff Kraff/Theoretical (SRK/T) and Barrett Universal II in predicting intraocular lens (IOL) power in Indian eyes. Methods: This retrospective study conducted in a tertiary care eye hospital. Data from patients having uneventful cataract surgery with Tecnis ZCB00 IOL implantation were obtained from Lenstar and electronic medical records. Eyes were divided into subgroups based on axial length (AL) as short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…However, they did not compare all the other formulas. Our results were different from those of Paritekar et al, [ 29 ] who found SRK/T and BU II to have lower MedAE and MAE than Kane formula for myopic eyes. This could be because they compared only 59 eyes in the myopic group (which they defined as AL >24 mm) and compared data at the end of 1 week instead of 1 month postoperatively.…”
Section: Discussioncontrasting
confidence: 99%
“…However, they did not compare all the other formulas. Our results were different from those of Paritekar et al, [ 29 ] who found SRK/T and BU II to have lower MedAE and MAE than Kane formula for myopic eyes. This could be because they compared only 59 eyes in the myopic group (which they defined as AL >24 mm) and compared data at the end of 1 week instead of 1 month postoperatively.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings suggest that there were modest differences between the formulas tested, with refractive prediction errors of approximately 0.32 D on the myopic side with the Hoffer Q, Kane, SRK/T, and Holladay 1 formulas. Similar findings were reported by Paritekar et al ( 17 ) in their study. Thus, the recommended lens constant for the Tecnis IOL should be altered for optimization.…”
Section: Discussionsupporting
confidence: 93%
“…The Kane (MAE 0.441 D) formula was the most accurate predictor of postoperative refractions in their study. However, research by Paritekar et al ( 17 ) on Indian populations demonstrated that the Kane formula did not exhibit significant advantages in short AL eyes, which was consistent with our findings. In our study, the Kane formula also did not show clear advantages in short eyes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Eyeballs are a cystic structure and almost spherical in shape [ 1 ]. The anterior and posterior diameter (axial length (AL)) is usually about 22-24 mm in the emmetropic eye [ 2 ]. The parallel rays of light from any image that enters the eye are focused on the retina by the refractive properties of the cornea and lens [ 3 ].…”
Section: Introductionmentioning
confidence: 99%